ROA, UKURAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN SEBAGAI DETERMINAN MANAJEMEN LABA: STUDI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Siti Mudawanah; Pindonta Nalsal (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2025)
Earnings management is the practice of manipulating financial reports carried out by companies in order to show that the company's performance is better than it actually is. This research aims to determine the influence of financial performance, company size and ownership structure on earnings management in manufacturing companies listed on the Indonesia Stock Exchange for the 2023 - 2024 period. The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange for the 2023 - 2024 period. Sample selection was carried out using a purposive sampling method which was selected using predetermined criteria and there were 54 companies that were the object of research with a total of 108 observations that met the criteria. The research method used is quantitative with the type of data used is secondary data. The analytical method used is the multiple linear regression analysis method using tools SPSS 25. The research results show that financial performance is proxied by ROA, company size and ownership structure as proxied by managerial ownership partially has a significant effect on earnings management, while ownership structure as proxied by institutional ownership have no effect on earnings management. And simultaneously ROA, Company size, managerial ownership and institutional ownership have a significant effect on earnings management in manufacturing companies listed on the IDX for the 2023 - 2024 period.